Rutin attenuates complete Freund’s adjuvant-induced inflammatory pain in rats - Fatemeh Forouzanfar; Ali Mohammad Pourbagher-Shahri; Amir Mahmoud Ahmadzadeh (Iranian Journal of Basic Medical Sciences)
Objective(s): Rutin is a bioflavonoid compound renowned for its anti-oxidative, anti-inflammatory, and antinociceptive properties. The present study aims to assess its therapeutic efficacy on complete Freund’s adjuvant (CFA)‑induced inflammatory pain. Materials and Methods: Arthritis was induced in Wistar rats via subcutaneous administration of CFA into the right hind paw. Rutin (15 and 30 mg/kg) and indomethacin (5 mg/kg, orally) were given once daily for three weeks. Parameters observed included alterations in paw swelling perimeter, arthritis scores, and body weight. Additionally, antinociceptive activity was measured through thermal hyperalgesia and cold allodynia responses. The Tumor necrosis factor-alpha (TNF-α) level in the serum was measured. Malondialdehyde (MDA), thiol levels, catalase, and superoxide dismutase (SOD) activities were also evaluated as serum oxidative stress markers. Results: Rutin and indomethacin significantly suppressed alterations in paw edema, pain responses, and arthritis scores and reduced the loss of body weight in contrast to disease-control rats. Furthermore, in contrast to disease control rats, rutin and indomethacin treatment exhibited an anti-inflammatory effect through a marked reduction in TNF-α levels in the serum. Rutin and indomethacin demonstrated a significant increase in catalase and SOD activities, a total thiol level, and a decrease in MDA level compared to the disease-control rats.Conclusion: These results suggest that rutin’s antiarthritic effect is mediated by its antinociceptive, anti-oxidant, and anti-inflammatory properties.